Abalos y Herreros : Parque litoral noroeste (2002)
Proyecto de renovación urbana en Barcelona con motivo del <Fórum>
Keywords: ABALOS-HERREROS; BARCELONA; ESPAÑA; ÁBALOS, IÑAKI; HERREROS, JUAN; PROYECTOS; PARQUES; PARQUES URBANOS